Pre-service mathematics teacher conducting prospective analysis: A case study on practice didactical design research - Jatisunda, Mohamad Gilar; Suryadi, Didi; Prabawanto, Sufyani; Umbara, Uba (IKIP Siliwangi and I-MES, 2025)
This study aims to understand how pre-service mathematics teachers conduct prospective analyses comprehensively. A qualitative research method with a case study design was used. The participant was Mrs N, a pre-service mathematics teacher who conducted research using DDR methodology in a grade 9 junior high school in Sindang, Majalengka, involving 48 students. Data were collected by analyzing empirical evidence from Mrs. N's prospective analysis process by uncovering the various stages of a prospective analysis. An iterative approach was used to analyze the data by refining the research questions through discussions and regular meetings with Mrs. N. The process ensured adaptability to new insights and understandings from the empirical data. Our findings reveal that the teacher draws upon fundamental philosophical principles from didactical design research, including hermeneutics, phenomenology, and ethnomethodology. By embracing these approaches, the teacher gains valuable insights into conducting research within an interpretive paradigm, allowing for a deeper exploration of the meaning of concepts, the purpose of learning, and the cultural influences that shape the educational process. Additionally, our study sheds light on the emergence of transpositional didactics theory as the prospective teacher delves into understanding the meaning of the geometrics transformation concept.